Postcranial anatomy of Pissarrachampsa sera (Crocodyliformes, Baurusuchidae) from the Late Cretaceous of Brazil: Insights on lifestyle and phylogenetic significance - Godoy, Pedro L.; Bronzati, Mario; Eltink, Estevan; Marsola, Jï¿½lio C. De A.; Cidade, Giovanne M.; Langer, Max C.; Montefeltro, Felipe C. [UNESP] (PeerJ, 2016)
The postcranial anatomy of Crocodyliformes has historically been neglected, as most descriptions are based solely on skulls. Yet, the significance of the postcranium in crocodyliforms evolution is reflected in the great lifestyle diversity exhibited by the group, with members ranging from terrestrial animals to semi-aquatic and fully marine forms. Recently, studies have emphasized the importance of the postcranium. Following this trend, here we present a detailed description of the postcranial elements of Pissarrachampsa sera (Mesoeucrocodylia, Baurusuchidae), from the Adamantina Formation (Bauru Group, Late Cretaceous of Brazil). The preserved elements include dorsal vertebrae, partial forelimb, pelvic girdle, and hindlimbs. Comparisons with the postcranial anatomy of baurusuchids and other crocodyliforms, together with body-size and mass estimates, lead to a better understanding of the paleobiology of Pissarrachampsa sera, including its terrestrial lifestyle and its role as a top predator. Furthermore, the complete absence of osteoderms in P. sera, a condition previously known only in marine crocodyliforms, suggests osteoderms very likely played a minor role in locomotion of baurusuchids, unlike other groups of terrestrial crocodyliforms. Finally, a phylogenetic analysis including the newly recognized postcranial features was carried out, and exploratory analyses were performed to investigate the influence of both cranial and postcranial characters in the phylogeny of Crocodyliformes. Our results suggest that crocodyliform relationships are mainly determined by cranial characters. However, this seems to be a consequence of the great number of missing entries in the data set with only postcranial characters and not of the lack of potential (or synapomorphies) for this kind of data to reflect the evolutionary history of Crocodyliformes.
Keywords: Adamantina formation; Bauru group; Baurusuchidae; Ecological habit; Fossil; Mesoeucrocodylia; Notosuchia; Osteoderms; Paleontology; Phylogenetic bias